Mother Tongue of Turkish Immigrant Children in Berlin: to Be or not to Be? - Hristo Kyuchukov (National Research University Higher School of Economics, 2018)
How do bilingual Turkish children develop their mother tongue knowledge in German kindergartens and what are some of the difficulties they face? These are the questions which this paper tries to answer. For this purpose, a study with Turkish kindergarten children from Berlin, Germany was conducted. A total of 40 children were divided into two groups between 3 and 6 years old and tested twice in a year with the TEDIL Test . The test consists of pictures and measures the knowledge of Turkish nouns, verbs, adjectives, prepositions, and syntax. All of the children were tested individually by a native Turkish speaker and by the researcher. The testing was done in the kindergarten setting. The results showed that the knowledge of both age groups on different grammatical categories in Turkish was equal on the first test and there were no statistical differences. However, during the second test the group of older children showed a decrease in their knowledge of the grammatical categories in their mother tongue. This paper discusses the factors that influenced the regression in the knowledge of Turkish. This study is one of only a few on bilingual Turkish children and it presents new information about mother tongue loss among kindergarten children, discusses the reasons, and suggests that kindergartens and families should cooperate and work together in order to prevent mother tongue loss from a very early age as well as its effect on the cognitive development of bilingual children.